Serine Supplementation Alleviates Doxorubicin-Induced Oxidative Damage in Skeletal Muscle of Mice - Chen, Jingqing; Zhou, Xihong; Jia, Hai; Wu, Zhenlong (Frontiers in Physiology, 2021)
Muscle weakness affects physical activity and quality of life of patients. Serine, a nutritionally non-essential amino acid has been reported to enhance protein synthesis and implicate in biosynthesis of multiple bioactive molecules. It remains unknown whether it can protect mice against oxidative stress-induced muscles weakness. This study was conducted to test the hypothesis that serine administration alleviates doxorubicin-induced oxidative damage in skeletal muscle of mice. Mice pre-treated with or without serine were intraperitoneally injected with either doxorubicin or equal volume of saline. Reactive oxygen species (ROS) accumulation, activity of antioxidant enzymes, oxidation product of protein, DNA, and lipid, activity of mitochondrial complex, and protein level of nuclear-factor-erythroid-2-related factor 2 (NRF2)/constitutive-androstane-receptor (CAR) signaling in skeletal muscle of mice were determined. Compared with the control, doxorubicin exposure led to oxidative damage as shown by increased ROS accumulation, decreased activity of antioxidant enzymes, and enhanced oxidative product of protein, DNA, and lipid in the skeletal muscle of mice. These effects of doxorubicin were associated with increased activity of complex I and reduced glutathione. Interestingly, doxorubicin-induced oxidative damage was alleviated by serine administration. Further study showed that the beneficial effect of serine was associated with enhanced NRF2/CAR signaling. Our result showed that serine attenuated doxorubicin-induced muscle weakness in mice. Serine supplementation might be a nutritional strategy to improve the function of skeletal muscle in patients exposed to doxorubicin.